2000
DOI: 10.1159/000028113
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Density of Cardiomyocytes in Chronic Nitric Oxide Synthesis Inhibition

Abstract: Objective: The myocardial effect on the normalization of arterial blood pressure in animals with hypertension previously induced by nitric oxide synthesis (NOS) inhibition is still unknown. The purpose of this study was to estimate the numerical density of cardiomyocytes that is able to show cardiomyocyte loss as a consequence of NOS inhibition. Methods: Sixty rats were divided into the following groups: control for 25 days (C25), control for 40 days (C40) control for 80 days (C80) and three other groups in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 29 publications
(33 reference statements)
2
27
0
Order By: Relevance
“…Counts are made into a frame of known area A T (considering the forbidden line and its extensions like described before). So, a test-volume is constructed (A T multiplied by thickness), count into this test-volume is considered unbiased (Gundersen et al 1988a, Mandarim-de-Lacerda and Costa 1993, Mandarim-de-Lacerda et al 1995, Burity et al 1996, Aguila and Mandarim-de-Lacerda 1999, Mandarim-de-Lacerda and Pereira 2000, Pessanha and Mandarim-de-Lacerda 2000, Melo et al 2002. The optical disector consists of counts made in thick sections observed with a light microscope adapted with axis-z mobile stage (to exactly determine the distance between up and down planes of the disector, or thickness t).…”
Section: Estimation Of Objets Quantitymentioning
confidence: 99%
“…Counts are made into a frame of known area A T (considering the forbidden line and its extensions like described before). So, a test-volume is constructed (A T multiplied by thickness), count into this test-volume is considered unbiased (Gundersen et al 1988a, Mandarim-de-Lacerda and Costa 1993, Mandarim-de-Lacerda et al 1995, Burity et al 1996, Aguila and Mandarim-de-Lacerda 1999, Mandarim-de-Lacerda and Pereira 2000, Pessanha and Mandarim-de-Lacerda 2000, Melo et al 2002. The optical disector consists of counts made in thick sections observed with a light microscope adapted with axis-z mobile stage (to exactly determine the distance between up and down planes of the disector, or thickness t).…”
Section: Estimation Of Objets Quantitymentioning
confidence: 99%
“…The chronic deficiency of nitric oxide (NO) causes arterial hypertension accompanied by cardiac hypertrophy, loss of cardiomyocytes, and changes in the myocardial microcirculation [19,25,26,27,28,29]. However, there is still controversy in relation to the exact interpretation of myocardial alterations caused by this model of arterial hypertension [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those reports, Ref. [41], [42] suggested that dilation and myocyte hyperplasia may be associated with the process of cardiac tissue remodeling. Reference [12] has reported chronic consumption of reheated palm oil induced cardiac toxicity but on the other hand, [43] suggested those events could be the results of toxicant production that had been induced by the lipid peroxidation of the palm oil.…”
Section: Discussionmentioning
confidence: 97%